The censures against Claudio Tozzi’s "Guevara,alive or dead..." (Palíndromo, 2017)
The news of Ernesto “Che” Guevara’s death incited the visual artist Claudio Tozzi to produce a series of panels in his honor. The first of these works, Guevara, alive or dead..., when exhibited at the IV Federal District Modern Art Salon in December 1967, was tagged by a right-wing group and violated by DOPS agents in an attempt to withdraw from the contest. This article proposes a speech, anchored in a phenomenological approach, on the panel in question and approaches it as a victim and witness of the State terrorism operated by the Brazilian military dictatorship (1964-1985), as well as crossed by a dynamic of projection of the Guevara’s image as a mask used by resistance to this regime. In addition, the work is analyzed from the censures it suffered: the first in the aforementioned Brasilia Salon in 1967 and the second, in an episode of self-censorship promoted by the jury, in the awarding of the prizes of the 17th Paulista Modern Art Salon.
Keywords: Claudio Tozzi; censorship; art and death; brazilian new figuration; appropriation